Micro Cell Culture Method for Isolation of Chlamydia trachomatis - McComb, Dorothy E. (1974)
Presterilized mictotiter plates (96 wells) with BHK-21 cells on 5-mm cover slips were successfully used for cell culture isolation of trachoma from 15 infected conjunctival scrapings.